2001
DOI: 10.1128/mcb.21.11.3840-3852.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Selenocysteine tRNA Maturation and Selenoprotein Synthesis in Transgenic Mice Expressing Isopentenyladenosine-Deficient Selenocysteine tRNA

Abstract: Selenocysteine (Sec) tRNA (tRNA([Ser]Sec)) serves as both the site of Sec biosynthesis and the adapter molecule for donation of this amino acid to protein. The consequences on selenoprotein biosynthesis of overexpressing either the wild type or a mutant tRNA([Ser]Sec) lacking the modified base, isopentenyladenosine, in its anticodon loop were examined by introducing multiple copies of the corresponding tRNA([Ser]Sec) genes into the mouse genome. Overexpression of wild-type tRNA([Ser]Sec) did not affect selenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 124 publications
(157 citation statements)
references
References 45 publications
7
149
1
Order By: Relevance
“…The ability to decode UGA as a Sec codon requires specific mRNA secondary structures and specific translational factors (Low and Berry, 1996;Berry et al, 2001) and is affected when tRNA [Ser]Sec lacks i 6 A at position 37, as demonstrated by Warner et al, 2000). Similarly, transgenic mice overexpressing i 6 A-deficient tRNA [Ser]Sec show defective levels of numerous selenoproteins due to problems occurring during translation and not transcription since mRNA levels remain unchanged (Moustafa et al, 2001). Many studies have correlated deregulation of protein biosynthesis with cancer, but it remains to be ascertained whether this process is necessary and/or sufficient for neoplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to decode UGA as a Sec codon requires specific mRNA secondary structures and specific translational factors (Low and Berry, 1996;Berry et al, 2001) and is affected when tRNA [Ser]Sec lacks i 6 A at position 37, as demonstrated by Warner et al, 2000). Similarly, transgenic mice overexpressing i 6 A-deficient tRNA [Ser]Sec show defective levels of numerous selenoproteins due to problems occurring during translation and not transcription since mRNA levels remain unchanged (Moustafa et al, 2001). Many studies have correlated deregulation of protein biosynthesis with cancer, but it remains to be ascertained whether this process is necessary and/or sufficient for neoplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…TR1 (cytosolic enzyme) and TR3 (this mitochondrial enzyme is also called TnxRd2 and TrxR2) expression was assessed by immunoblot assays with antibodies specific for each isozyme, after the enzymes were enriched by binding to ADP-Sepharose as described previously (Moustafa et al, 2001). Expression of SelR, GPx1, and Sep15 was analysed by immunoblot assays with antibodies specific for these proteins.…”
Section: Selenoprotein Expression Analysesmentioning
confidence: 99%
“…PSTK or thioredoxin containing a His-tag, which was used as a control protein, was added in a total volume of 100 l containing reaction mixture (see above) with or without 50 M unlabeled ATP and 500 ng of a highly purified sample of a mixture of both tRNA [ After washing three times with 1 ml of 1ϫ TBS͞0.1% Tween, the beads were suspended in 40 l of TBE-urea loading buffer (90 mM Tris͞64.6 mM boric acid͞2.5 mM EDTA͞3.5 M urea, pH 8.3), and 5 l of each sample was loaded onto a 15% TBE-urea gel. After electrophoresis and transfer of the RNA to a nylon membrane, RNA was detected by Northern blotting with the appropriate probe (17).…”
mentioning
confidence: 99%